PHYTOEXTRACTION OF CADMIUM AND LEAD FROM A CONTAMINATED SOIL USING EUCALYPTUS SEEDLINGS - & Ibrahim, Al-Salmany (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
This study aims to estimate critical concentrations of cadmium (Cd) and lead (Pb) in the soil which negatively affect growth of Eucalyptus camaldulensis Dehnh. seedlings, and to estimate some phytoextraction parameters for heavy metals (HM) from the soil to evaluate efficiency of seedlings in their potential use in phytotechnology to improve the environment with phytoremediation. Eucalyptus seedlings were treated with Cd concentrations 0, 25, 55, 85, and 110 mg kg-1 dry soil as CdCl2, and Pb concentrations 0, 125, 250, 450, and 550 mg kg-1 dry soil as PbCl2, and the experiment was designed using the completely randomized design (CRD) as a two-factor factorial experiments and the data were analyzed using SAS system. Results showed that the highest percentage decrease in dry weight of stems, leaves and roots were 55, 68.6, and 67.2%, respectively, at the interaction (110 Cd and 550 Pb) mg kg-1 dry soil compared with control, and Cd concentrations in stems, leaves and roots ranged between (0.375-372.167), (0.417-128.167) and (0.583-162.083) mg kg-1, respectively and Pb concentrations in stems, leaves and roots ranged between (9.583-62.375), (10.042-20.417) and (2.875-73.500) mg kg-1. It was found that values ​​of translocation factor (TF), biological accumulation coefficient (BAC), bioconcentration factor (BCF) and concentration index (CI) for Cd ranged between (0.611-4.239), (1.333-28.790), (0.383- 16.840) and (1-490.812) respectively, and values ​​of TF, BAC, BCF, and CI of Pb ranged between (0.275-5.702), (0.769-4.246), (0.295-7.539) and (1-3.833) respectively, and tolerance index (TI) values ​​ranged between (0.370-1). We concluded that Eucalyptus seedlings are suitable for phytoextraction applications within phytoremediation processes of soils contaminated with Cd and Pb.